2019
DOI: 10.1080/21691401.2019.1687502
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast promotes mitochondrial biogenesis via CREB/PGC-1α in human bronchial epithelial cells

Abstract: Bronchial epithelial mitochondrial dysfunction including impaired mitochondrial biogenesis has been linked with the initiation and development of bronchial asthma. Montelukast, a robust antagonist of cysteinyl leukotriene receptors, has been widely applied for the therapies of bronchial asthma. However, the effects of montelukast in airway epithelial mitochondrial dysfunction are less reported. In the present study, we report that montelukast treatment in human bronchial epithelial cells of Beas-2b increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…It can also regulate the key mitochondrial genes involved in adaptive thermogenesis by coordinating the expression of a large number of genes involved in glucose and fatty acid metabolism. Studies have shown that the clinical drugs used to improve breathing, such as aminophylline and montelukast, can promote the biogenesis of human alveolar epithelium mitochondria through cAMP responsive element binding protein (CREB)/PGC-1α (Wang et al, 2019;Wei et al, 2019). The use of the mitochondrial antioxidant resveratrol can protect mtDNA and reduce apoptosis through SIRT1-PGC-1a (Wang et al, 2020;Zhu et al, 2021).…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%
“…It can also regulate the key mitochondrial genes involved in adaptive thermogenesis by coordinating the expression of a large number of genes involved in glucose and fatty acid metabolism. Studies have shown that the clinical drugs used to improve breathing, such as aminophylline and montelukast, can promote the biogenesis of human alveolar epithelium mitochondria through cAMP responsive element binding protein (CREB)/PGC-1α (Wang et al, 2019;Wei et al, 2019). The use of the mitochondrial antioxidant resveratrol can protect mtDNA and reduce apoptosis through SIRT1-PGC-1a (Wang et al, 2020;Zhu et al, 2021).…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%
“…Although the impact of LT signaling on autophagy or mitochondria is largely unresearched in neurodegenerative diseases, studies on non-neurological conditions suggest detrimental effects of LTs on the autophagic and mitochondrial system [113][114][115][116][117][118].…”
Section: The Contribution Of Leukotrienes In Autophagic Activity Impa...mentioning
confidence: 99%
“…Notably, LT signaling seems to affect mitochondrial function at the CysLT 1 R as well as at the BLTR 1 level [116][117][118]. On the one hand, the intraperitoneal administration of the BLTR 1 inhibitor U75302 reversed mitochondrial complex I and II downregulation and attenuated mitochondrial impairment in the myocardium of an LPS-induced acute cardiac injury mouse model [116].…”
Section: The Contribution Of Leukotrienes In Autophagic Activity Impa...mentioning
confidence: 99%
See 1 more Smart Citation
“…These results support a role for oxidative stress during COVID-19. Importantly, protective effects of MK are not limited to inflammatory and microbial infectious attacks, but also include protection against chemotoxicity (bleomycin, cysplatin, doxorubicin, statin, paracetamol) (Hareedy et al, 2019) and radiotoxicity (Hormati et al, 2020) in animal experiments, which demonstrates some antioxidant properties resulting in increased mitochondrial mass and functionality, together with increased intracellular cyclic adenosine 3, 5′-monophosphate (cAMP) level and activation of the Krebs cycle (Wang et al, 2019).…”
Section: Properties Of Mk Related To Tissue Sequelae Antioxidant Propmentioning
confidence: 99%